ALIH KODE DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Aditya Permana, - (2023)
Code switching is a phenomenon that is common among bilingual students. Learning Indonesian by using two languages as the language of instruction raises the phenomenon of code switching in it. This study aims to analyze the forms, types and factors of teacher code-switching in Indonesian language learning, as well as identify teacher conceptions of using code-switching in Indonesian language learning in the early upper grades of elementary school. This research uses a qualitative method with a phenomenology method. Participants in this study were 3 class IV teachers. The data in this study are in the form of teacher speech events in Indonesian language learning in class IV of elementary school. Data is collected by paying attention to the course of the learning process in class. Based on the results of the research, it shows that (1) the form of code switching that is identified is a form of internal code switching, where the teacher switches the language from the National Language to the Regional Language. (2) The types of code switching found in this study are (a) tag switching, in the form of expressions and exclamations. (b) Intra-sentential switching, where the teacher accidentally inserts a word, clause or phrase of a different language in one complete sentence. (c) Inter-sentential switching, seen from the existence of complete sentences that are in a different language from the sentences that surround them. (3) The factors of using code switching that were found were situational and metaphorical, where situational was due to language switching because of the speech partners or participants and metaphorical was switching languages due to switching topiks or the purpose of the conversation. (4) The teacher's perception of code switching is to facilitating communication and makes it easier for teachers to convey material contextually so students can easily understand.